Teeth Eruption Disorders: A Critical Review - Panagiotis Roulias; Nikolaos Kalantzis; Dafni Doukaki; Aspasia Pachiou; Konstantinos Karamesinis; George Damanakis; Sotiria Gizani; Apostolos I. Tsolakis (Children, 2022)
Dental eruption refers to the vertical displacement of a tooth from its initial non-functional towards its functional position. Tooth eruption disorders may be expressed in various clinical conditions, which may be grouped as “primary retention” and “secondary retention”. The purpose of this article is to review the literature and the clinical parameters of the various conditions related to tooth eruption disorders. Materials and Methods: The search strategy of this critical review included keywords in combination with MeSH terms in Medline, Scopus, and Cochrane Library until February 2022 and only in English. Results: “Primary Failure of Eruption” (PFE) occurs during the eruption process and includes clinical characteristics of both primary and secondary retention, which make diagnosis difficult. PFE is distinguished by Types I and II. In Type I, the defect in the eruption process occurs in all the relative teeth at the same time, whilst in Type II, the clinical expressions vary in multiple quadrants of the mouth, and the second molars erupt more. The variability of the PFE’s clinical spectrum seems to be connected to a genetic origin. The differential diagnosis among single ankylosis, secondary retention, and PFE is based on the occlusal relationship between the upper and the lower teeth distally, most commonly the first molar, which has not yet fully erupted. The treatment approach depends on many factors and combines surgical and orthodontic techniques.